(untitled) (Canadian Medical Education Journal, 2021)
Background: Focused objectives provide effective learning. Pediatric residents in Canada follow objectives set by the Royal College of Physicians and Surgeons of Canada (RCPSC) with the goal of becoming competent general pediatricians. During the gastroenterology rotation, it remains unclear as to what clinical problems listed in the aforementioned objectives are crucial to understand as part of general pediatric practice. The purpose of this study was to identify the gastroenterological conditions of most importance to incorporate into a focused curriculum for pediatric residents. Methods: All pediatricians across four Canadian Atlantic provinces were surveyed by a mailed questionnaire. Questions included demographics and ranking of the 14 clinical problems currently listed in the RCPSC objectives along with six more generated after input was gained from pediatric gastroenterologists. Results: Of the 234 pediatricians surveyed, 132 (56%) responded, 48% of whom were general pediatricians. Celiac disease, gastroesophageal reflux, and obesity (currently not on the RCPSC list) were identified as important/very important conditions to understand by 94.4%, 96.1%, and 96.0% of respondents, respectively. There were no significant differences in rankings between general pediatricians and subspecialists. A large majority recommended that a rotation in gastroenterology be mandatory during pediatric residency. Conclusions: Pediatricians from four Canadian Atlantic provinces recommended a list of gastrointestinal conditions to be included in pediatric residency training. It would be important to consider these recommendations to keep the training curriculum in sync with real world needs.